2018
DOI: 10.37358/rc.18.8.6448
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Active Properties Evaluation of Wild Oregano (Origanum Vulgare) and Ginger (Zingiber Officinale-Roscoe) Essential Oils

Abstract: The compounds in Ginger (Zingiber officinale-Roscoe) essential oil provenience China and wild oregano (Origanum vulgare) essential oil of Romanian origin were identified by GC/MS and their antioxidant and antifungal properties were evaluated. Wild oregano oil was characterized by high content of oxygenated monoterpenes hydrocarbons (84.05%) of which carvacrol was the most abundant (73.85%) followed by b-linalool (3.46%) and thymol (2.29%). Ginger oil had a higher content of sesquiterpene hydrocarbons including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…However, different studies reported an antifungal activity of plants belonging to Origanum genus. For example, O. dictamnus essential oil is active against the growth of B. cinerea [16]; O. vulgare against P. expansum [17,18] and O. minutiflorum against A. niger [19].…”
Section: Resultsmentioning
confidence: 99%
“…However, different studies reported an antifungal activity of plants belonging to Origanum genus. For example, O. dictamnus essential oil is active against the growth of B. cinerea [16]; O. vulgare against P. expansum [17,18] and O. minutiflorum against A. niger [19].…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidant activity test by DPPH method was performed according to a previous method used by others [21][22][23][30][31][32]. Briefly, the compounds to be tested were dissolved in methanol at concentrations of 2; 4; 8; 16, and 32 μM.…”
Section: Antioxidant Activity Testmentioning
confidence: 99%
“…In this study, we aimed to determine the chemical reactivity of the organotin(IV) carboxylate compounds diphenyltin(IV) di-4-aminobenzoate and triphenyltin(IV) 4-aminobenzoate by using cyclic volta-mmetry. We also examined the antioxidant properties of these compounds using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method using a similar procedure applied by others [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Ginger is the rhizome of Zingiber officinale Roscoe belonging to the family of Zingiberaceae and is native in Asia but also grown in Africa, India and other tropical regions [ 33 ]. Z. officinale Roscoe is primarily used in the management of nausea, but it is also used as an anti-inflammatory, a pain remedy, a warming remedy and a cholesterol-lowering herb [ 34 ].…”
Section: Introductionmentioning
confidence: 99%